Cover Image, Volume 85, Issue 6. Issue 6 (June 2017) - Olechnovič, Kliment; Venclovas, Česlovas
Abstract : The cover image, by Kliment Olechnovič and Česlovas Venclovas, is based on the Article VoroMQA: Assessment of protein structure quality using interatomic contact areas DOI:10.1002/prot.25278 .